Observations on Growth and early Production of some Durian (Durio zibethinus Murr) Clones at Universiti Pertanian Malaysia Orchard - Yaacob, Othman; Talib, Awaluddin; Ismail, Mohd. Noor (1978)
The establishment of a 22 acre durian orchard on an oxisol soil formerly under old rubber is recorded outlining the nature of the environment and the cultural practices adopted since 1969. The growth pattern of all clones planted, early flowering and fruiting patterns are also discussed together with possible causes of poor fruiting habits of D2 and D96. Some possible areas for research are suggested for future work based on these observations.